2020
DOI: 10.1074/mcp.ra120.001955
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Genetics of AGC-kinases Reveals Shared Targets of Ypk1, Protein Kinase A and Sch9

Abstract: Protein phosphorylation cascades play a central role in the regulation of cell growth and protein kinases PKA, Sch9 and Ypk1 take center stage in regulating this process in S. cerevisiae. To understand how these kinases co-ordinately regulate cellular functions we compared the phospho-proteome of exponentially growing cells without and with acute chemical inhibition of PKA, Sch9 and Ypk1. Sites hypo-phosphorylated upon PKA and Sch9 inhibition were preferentially located in RRxS/T-motifs suggesting that many ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 77 publications
(117 reference statements)
0
12
0
Order By: Relevance
“…Importantly, however, not all known PKA targets were affected by rapamycin treatment, which was validated for a subset [ 25 ]. Similarly, we found that some, but not all sites hypo-phosphorylated upon PKA inhibition were also hypo-phosphorylated upon Sch9 inhibition [ 163 ]. No bona fide unique Sch9 site is known to date and the sites shared with PKA reside in the R[R/K]x[S/T] motif [ 94 , 120 ].…”
Section: Substrate Specificity Of Pka and Sch9mentioning
confidence: 85%
“…Importantly, however, not all known PKA targets were affected by rapamycin treatment, which was validated for a subset [ 25 ]. Similarly, we found that some, but not all sites hypo-phosphorylated upon PKA inhibition were also hypo-phosphorylated upon Sch9 inhibition [ 163 ]. No bona fide unique Sch9 site is known to date and the sites shared with PKA reside in the R[R/K]x[S/T] motif [ 94 , 120 ].…”
Section: Substrate Specificity Of Pka and Sch9mentioning
confidence: 85%
“…Therefore, in addition to Ypk1, some other as yet unidentified protein kinase in the Ypk1-as-(His) 6 -HA preparation is capable of phosphorylating these proteins at these specific sites. In this regard, it has been reported recently that some targets that contain sequences that harbor within them the Ypk1 consensus can also be phosphorylated by other AGC family protein kinases, including•PKA and Sch9 [59]. We have not yet tested the Ypk1-as-(His) 6 -HA preparation for the presence of either of these potential contaminants.…”
Section: Localization Of β-Propeller Proteins Laf1 and Dgr2 At Er-pm mentioning
confidence: 98%
“…The roles of PKA and TORC1 seem to be rather temporally than functionally distinct (Kunkel et al ., 2019). We did not specifically investigate the role of TORC2 signaling for the program reflected by the PT score but do not exclude a potential influence, since TORC2 was recently shown to share common targets with PKA and TORC1 via its downstream kinase Ypk1 (Plank et al, 2020). Other pathways, including AMPK/Snf1 signaling, regulate overlapping processes and cross-talk with PKA and TOR but affect limited sets of proteins if modulated independently (Kingsbury et al ., 2015; Malecki et al ., 2020; Zaman et al, 2009).…”
Section: Discussionmentioning
confidence: 99%